The right to live and the right to die? - Willy F. Maramis (JURNAL WIDYA MEDIKA, 2014)
With the advance of medical science and technology, dying can be postponed now. For how long and how is the quality of life? Frequently modern medicine postpones death only, while leaving the quality of life of many patients in a questionable state. Do we have the right to live? Where do we get that right from? The right to live is inherent to our nature of being alive. With right comes obligation. What about the right to die? Some say if there is the right to live, there must also be the right to die. What is life and what is death anyway? Some say death is part of life. Death is in fact the absence of life. We can measure life, but we can not measure death. It’s like stating that darkness is part of light. Also, if there is the right to die, what obligations on earth does a dead person have? ‘The right to live’ excludes ‘the right to die’. This moral philosophical approach is only following our moral-ethical reasoning (not our emotions). If we have ‘the right to die’, it is not far from having ‘the right to kill’ or may be ‘the duty to die’. The battle between the pros and the cons on the right to die is not over yet. We may consider the transcendental approach. When curative medicine is of no benefit anymore, care giving and ministering medicine must take its place. The transcendental approach takes the dying person as a bio-psycho-socio-cultural-spiritual being with the belief in life after death, and the ‘exit’ is with faith, hope and love. It is much more optimistic and relieving than the worldly approaches with an ‘exit’ because of despair.